Global Behavior of the Max-Type Difference Equation xn+1=max⁡{1/xn,An/xn−1} - Taixiang Sun; Bin Qin; Hongjian Xi; Caihong Han (Abstract and Applied Analysis)
We study global behavior of the following max-type difference equation xn+1=max⁡{1/xn,An/xn−1}, n=0,1,…, where Ann=0∞ is a sequence of positive real numbers with 0≤inf⁡An≤sup⁡An<1. The special case when Ann=0∞ is a periodic sequence with period k and An∈(0,1) for every n≥0 has been completely investigated by Y. Chen. Here we extend his results to the general case.